THE DEVELOPMENT OF TEACHABLE MACHINE-ASSISTED MODULES TO IMPROVE STUDENTS' COMMUNICATION WRITING SKILLS IN JUNIOR HIGH SCHOOL - Zainur Rasyid Ridlo; Rusdianto Rusdianto; M. Ulul Albab Kholifatul Ardli; Dwi Wahyuni; Silvi Putri Ayu Ningsih; Joko Waluyo (PENDIDIKAN SAINS DAN TEKNOLOGI, 2026)
Communication writing skills are a person's ability to communicate ideas, information, or thoughts through writing in a clear, structured, and effective manner. This study aims to examine the validity, practicality, and effectiveness of the Teachable machine-assisted module in improving junior high school students' communication writing skills. This study is a Research and Development (R&D) study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The techniques used to collect data on validity, practicality, and effectiveness were validation sheets, observation sheets, tests, and student response questionnaires. Expert validation showed that this module was “highly valid” in terms of graphics, language, and content, with an average percentage of 86%. Practicality tests in the classroom showed that this module was very practical, with a score of 88%. The results of the effectiveness analysis showed a significant increase in written communication skills, particularly in the indicators of changing presentation and analyzing tables, with N-gain scores of 0.67 (moderate category) respectively. The student response questionnaire reinforced the effectiveness of this module, with an average positive response of 83%. Overall, this Teachable Machine-based module is effective and suitable for use as science teaching material, despite challenges in adapting the use of technology and written communication skills.